Implementation Of Wakaf As A Tool Of Social Finance To Achieve The SDGs In Indonesia Case Study On Indonesian Waqf Board - Nst, Venny Fraya Hartin; Nasution, Yenni Samri Juliati; Siregar, Saparuddin (Moneter: Jurnal Keuangan dan Perbankan, 2024)
This research found several gaps related to the implementation of waqf as a social financing tool to achieve SDGs in Indonesia (a case study on the Indonesian Waqf Board), among others: Lack of Research on the Linkage of Waqf and SDGs. Most research on waqf in Indonesia focuses on the legal, management, and implementation aspects in general. However, very few explore the relationship between waqf as a social financing instrument and its purpose to support the achievement of Sustainable Development Goals (SDGs). Problem formulations are 1) An exploration of the Indonesian Waqf Board, and the importance of waqf as a social financing tool, as well as its potential future development and expansion; 2) Challenges and opportunities in utilizing waqf for social financing as well as issues related to governance, transparency, and sustainability. Qualitative research method with descriptive analysis method in the form of explanation. Research Results BWI has successfully demonstrated how waqf can be utilized to fund various social programs that support the achievement of SDGs, such as education, health, and economic empowerment. Although it still faces a number of challenges, the opportunity to develop waqf as a social financing tool is enormous, especially with the utilization of technology and increased collaboration with the private sector and government. With efforts to improve regulation, management capacity, and community participation, waqf can become a more effective instrument in achieving sustainable development in Indonesia.